2018
DOI: 10.3892/br.2018.1040
|View full text |Cite
|
Sign up to set email alerts
|

Common mental disorders and association with telomere length (Review)

Abstract: Telomeres are repeated 5′-TTAGGG-3′ sequences at the end of chromosomes, which maintain genomic stability. Their length is related to a number of diseases that affect humans. Apart from cancer, cardiovascular diseases, diabetes and other, telomere length has been associated with chronic diseases. Chronic mental illness includes various types of mental disorders with the most common being depression, schizophrenia and stress-anxiety. The aim of this review is to summarize the current state of knowledge on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 82 publications
0
32
1
Order By: Relevance
“…A growing body of literature links short TL from peripheral proxy tissues, such as leukocytes, with the onset and progression of neurodegenerative and psychiatric disorders, and chronic stress (27,55,(64)(65)(66). However, in the present study stress reactivity, although influential in heart telomere length, did not affect the rate of telomere attrition in the brain.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…A growing body of literature links short TL from peripheral proxy tissues, such as leukocytes, with the onset and progression of neurodegenerative and psychiatric disorders, and chronic stress (27,55,(64)(65)(66). However, in the present study stress reactivity, although influential in heart telomere length, did not affect the rate of telomere attrition in the brain.…”
Section: Discussioncontrasting
confidence: 74%
“…Interestingly, the likelihood of onset and progression of age-related diseases is associated with an anxious personality (19)(20)(21) and HPA axis dysfunction (22,23). It is therefore thought that an exacerbated stress response may contribute to telomere shortening, accelerated ageing and, in turn, age-related disease (24)(25)(26)(27)(28). Additionally, telomere shortening can influence replicative senescence indirectly via downstream regulators such as SMAD specific E3 ubiquitin-ligase 3 (Smurf2) (29,30) thus telomere length might be mediating other physiological aspects associated with ageing.…”
Section: Introductionmentioning
confidence: 99%
“…TL and telomerase activity are strongly associated with human health as they have been linked to several age-related diseases, such as cancer, cardiovascular disease (CAD), diabetes, rheumatoid arthritis and psychiatric disorders (34)(35)(36)(37)(38). Moreover, previous studies have suggested that female human fertility decreases with an increased maternal age and that various adverse factors, including reduced telomerase activity, can contribute to age-associated infertility in women (39,40).…”
Section: Role Of Telomeres and Telomerase In Agingmentioning
confidence: 99%
“…Telomeres are highly conserved non-coding tandem repeats (5'-TTAGGG-3') located at the extreme end of chromosomes, coated by a complex of 6 proteins, termed the 'shelterin complex' and they are essential for genomic stability and integrity. The telomeric length of human germ cells (10-20 kb) is longer compared to that of human somatic cells (5-10 kb) (1). Telomeric length is heritable and varies with sex, as females have longer telomeres due to the presence of estrogen (2).…”
Section: Introductionmentioning
confidence: 99%